New results on the robust stability of control systems with a generalized disturbance observer. Issue 6 (30th July 2019) - Nie, Zhuo‐Yun; Wang, Qing‐Guo; She, Jinhua; Liu, Rui‐Juan; Guo, Dong‐Sheng
Abstract: A generalized disturbance observer‐based (GDOB) control system and its robust stability are studied in this paper. One feature of this new GDOB scheme is that an inverse of the nominal plant in the standard DOB is no longer required. Thus, it is applicable to both minimum‐phase (MP) and non‐minimum‐phase (NMP) plants. New conditions for robust stability are derived for two cases: plants with no right half plane (RHP) zero and plants with no RHP pole, which are in a perfect dual form. The duality reveals that the robust stability for a plant with RHP zeros is met when the Q ‐filter has a sufficiently large constant. This is fundamentally different from well‐known results for a MP plant. The stability conditions indicate that the robustness against large uncertainties not only can be achieved by a well‐selected Q ‐filter, but also by the reduction of mismatch between a compensated plant and a desired model. The obtained stability results provide guidelines for the control system design. This is illustrated by three examples.